Аpplicability of microsatellite loci designed for cosmopolitan species for the investigation of endemic species: a case study of Silene sendtneri Boiss. - Jasna Hanjalić; Lejla Ušanović; Lejla Lasić; Abdurahim Kalajdžić; Belma Kalamujić Stroil; Adisa Ahmić; Naris Pojskić (Glasnik Šumarskog Fakulteta Univerziteta u Banjoj Luci)
Silene sendtneri Boiss. (Caryophyllaceae) is the Dinaric endemic plant species with white, decorative and scented flowers. Previous studies on this endemic species were based on morphology and effects on seed germination after the treatment with salicylic acid. However, no molecular genetic studies have been conducted on this species so far. This paper presents preliminary results of the usefulness of microsatellite loci created for cosmopolitan species in assessing the genetic diversity of endemic plant species. A total of 100 specimens were collected from 18 localities in the mountain regions of Treskavica, Igman, Bjelašnica and Ozren in Bosnia and Herzegovina. No S. sendtneri individuals were found at the mountain Trebević. We tested cross-amplification success and a polymorphism level for the set of microsatellite markers (Sil01, Sil03, Sil16, Sil31, Sil35) designed for the cosmopolitan species Silene nutans. In 100 analyzed individuals of S. sendtneri, Sil31 and Sil35 did not amplify, Sil01 was monomorphic and the remaining two loci showed a high level of allelic diversity. Our findings suggest that caution should therefore be exercised in selecting microsatellite markers designed for cosmopolitan plant species in the analyses of endemic species of the same genus since different genetic factors affect the amplification success and polymorphism of the given loci. Attention should be given to the number of detected and effective alleles and their ratio, the success of locus amplification concerning the complete set of markers used, and the ratio of polymorphs to the total number of observed loci.